SILAR deposited nanocrystalline ZnO films as LPG sensor. (2021) - Gonugade, M.D.; Powar, S.B.; Salokhe, B.S.; Lokhande, C.D.; Kim, J.H.; Gurav, K.V.
Abstract: A facile successive ionic layer adsorption and reaction (SILAR) method is used for the deposition of nanocrystalline zinc oxide (ZnO) thin films. The XRD pattern shows ZnO films are polycrystalline in nature with wurtzite crystal structure. The surface morphology reveals ZnO nanograins embedded conical morphology, which shows hydrophobic behavior. The Liquefied Petroleum Gas (LPG) sensing properties of nanocrystalline ZnO films are investigated. The nanograined ZnO thin film shows maximum gas response of 20% at 673 K upon exposure to 5200 ppm of LPG.